UPACARA HANTA UA PUA UNTUK MEMPERINGATI MASUKNYA ISLAM DI DANA MBOJO - Nurnazmi Nurnazmi; Ali Maksum (Pustaka Peradaban, 2023)
Bima officially became an Islamic kingdom since 1050 H / 1640 AD, king Rumata Mabata Wadu / La Ka'i changed his name to Abdul Kahir I (would become the first Sultan of Bima). To strengthen the agreement in Oi Ule and broadcasting the development of Islam in Bima, three activities were established, namely (1) the Hanta Ua Pua ceremony to celebrate the Maulud of the Prophet Muhammad SAW, (2) Aru Raja To'i (Eid al-Fitr), and (3) Aru Raja Na'e (Eid al-Adhar). Hanta ua pua is a traditional ceremony that is closely related to the history of converting to Islam in the land of Bima. The hanta ua pua ceremony process is complemented by uma lige, dolu flowers, Wera jara and jara sara'u troops, suba na'e warriors, lenggo dance, kanja and mihu dances, sere dances, and dali. The objectives to be achieved in upcara hanta ua pua, as follows: (1) Commemorating and glorifying the birth day of the Great Prophet Muhammad Saw, (2) Commemorating the entry of Islam and the establishment of the Bima Sultanate, and (3) Honoring the Malay penghulu (Datuk gurunya) and all his family / descendants who contributed to spreading Islam in Bima. Bima resmi menjadi kerajaan islam sejak tahun 1050 H/ 1640 M, raja Rumata Mabata Wadu/ La Ka’i merubah namanya menjadi Abdul Kahir I (bakal menjadi Sultan Bima pertama). Untuk memperkokoh perjanjian di Oi Ule dan penyiaran pengembangan Islam di Bima ditetapkan tiga kegiatan yaitu (1) upacara Hanta Ua Pua untuk merayakan Maulud Nabi Muhammad SAW, (2) Aru Raja To’i (Hari Raya Idul Fitri), dan (3) Aru Raja Na’e (Hari Raya Idul Adhar). Hanta ua pua merupakan upacara adat yang erat kaitannya dengan sejarah masuk agama Islam ditanah Bima. Proses upacara hanta ua pua dilengkapi dengan uma lige, bunga dolu, pasukan jara Wera dan jara sara’u, laskar suba na’e, tari lenggo, tari kanja dan mihu, tari sere, dan dali. Tujuan yang ingin dicapai dalam upcara hanta ua pua, sebagai berikut: (1) Memperingati dan memuliakan hari kelahiran Nabi Besar Muhammad Saw, (2) Memperingati masuknya agama Islam dan berdirinya Kesultanan Bima, dan (3) Menghormati penghulu Melayu (Datuk gurunya) beserta seluruh kaum keluarga/ keturunannya yang berjasa menyebarkan agama Islam di Bima.